SOVIET LEGACY AND IMAGINED PAST CONVERGE IN LEVANT BATTLEFIELDS - Guliyev, Etibar (Wydawnictwo Naukowe WNPiD UAM, 2021)
The article analyzes main drivers of the revitalization of the Soviet ideological narratives in Uzbekistan and Tajikistan. A key impetus for the study has been ever increasing number of the terrorist attacks claiming dozens of lives in Russia committed by Central Asian originated fighters as well as arrest of dozens of members of the various religious organizations banned in Uzbekistan and Tajikistan. The hypothesis rests on the assumption that ideological cacophony stemming from deep controversies embodied in the refashioned Soviet ideological narratives to me major cause of the problem. While employing the path dependence approach, I mainly point to interaction between the surge in the religious extremism and ideological disorientation caused by ideological disorientation in the region continuing since the breakdown of the Soviet Union in 1991 to address main research question “what are external implications of post-Soviet ideological narratives in Uzbekistan and Tajikistan?.” The paper finds out that the post-independent identity policies are not designed to build a new idea but to moot or keep at arms-length identities marginalized during the Soviet period. The Soviet legacy constitutes the core of the neo-ethnic identities introduced by former communist leaders just slightly refashioned with highly selective and politically motivated supplements. Sharp contradictions embodied in these narratives designed to ensure policy goals is among drivers of the ideological disorientation which in its turn acts as a breeding ground for the recruitment of Uzbek and Tajik youth to the global terrorist networks. © 2021 Wydawnictwo Naukowe WNPiD UAM. All rights reserved.
SOWIECKIE DZIEDZICTWO I WYIMAGINOWANA PRZESZ?O?? SKUPIONE NA POLU BITWY LEWANTU
Keywords: Central Asia; Identity; Path dependence; Soviet legacy; Terrorism